Analysis of Impact of Management Control Systems (MCS) on Productivity and Approach to Determining Strength of MCS for Road PPP Projects. (June 2014) - Mony, Suresh; Aparna, A.
Expectations that public–private partnerships (PPPs) in roads will alleviate time overruns and enhance project productivity in India have not materialised. Substantial delays in tackling the attendant risks in the life cycle of the road PPP have occurred presumably because of weak management control systems (MCS) to mitigate risks. Very little research has been done on the influence of MCS on productivity. This article attempts to establish a relationship between MCS and project productivity. A strength index of MCS to serve as a strategic control mechanism is also presented.